APLIKASI MANAJEMEN KEUANGAN PADA UMKM TELUR ASIN DI DESA KEBONSARI KABUPATEN SIDOARJO - Yulia Tri Rahkadima; Medya Ayunda Fitri; Rina Sri Wulandari (Universitas Nahdlatul Ulama Sidoarjo, 2019)
Duck breeders are the main occupation from the majority of Kebonsari villagers in Candi, Sidoarjo Regency. They process the eggs which are produced into salted eggs by various methods such as steamed, oven and grilled and salted eggs produced have a variety of flavors. One obstacle in developing their business is the lack of knowledge related to business financial management. Financial management training is conducted to enhance knowledge related to the importance of financial management and how to create a correct balance sheet. The result of the training that has been done is that now each member has their own balance sheet and can evaluate the business that has been run. It is expected that after this activity, each cooperative member understands how to develop their business effectively and efficiently based on the financial balance analysis they make.